ISOLASI DAN UJI AKTIVITAS BAKTERI SELULOLITIK DARI AIR MUARA DAERAH ALIRAN SUNGAI SIAK WILAYAH KABUPATEN BENGKALIS - Sarlly Deviani; Yuli Haryani; Christine Jose (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cellulolytic bacteria are bacteria that can degrade cellulose into smaller polysaccharides called cellodextrins or completely into glucose units. Glucose is used as a carbon source for bacterial growth. The aims of this study were to isolate cellulolytic bacteria from estuary water of Siak watershed in Bengkalis area and to determine its cellulolytic activity and specific activity. A total of 13 isolates of cellulolytic bacteria have been isolated using commercial cellulose substrate containing 1% w/v carboxymethyl cellulose (CMC). We found that 11 of the 13 isolates were Gram negative bacteria, while others were Gram positive. The isolate of C3 from Pelabuhan Roro showed the highest cellulolytic activity [(1.701 ± 0.166) x 10-3 U/mL] which was not significantly different (p≤0.05) with cellulolytic activity of the A3 isolate [(1.605 ± 0.041) x 10-3 U/mL]. The C3 isolate also had the highest Cellulolytic specific activity [ (31.037 ± 4026) x 10-3 U/mg] and it was significant (p≥0.05) different with other isolates